Multibacterial Growth From a Surgical Renal Stone Culture: A Case Report and Literature Review - Mufarrij, Patrick W (MedReviews, LLC, 2012)
Urinary calculi may harbor bacteria, and this may lead to deleterious events during stone fragmentation and removal. The isolation of such bacteria from surgically extracted calculi allows for the specific tailoring of antimicrobial therapy. Here, we describe a case involving percutaneous stone removal from which the stone culture demonstrated growth of five different microorganisms. The results of this culture prompted a change in the antibiotic coverage, resulting in a more targeted treatment and improved patient care.